Observational evidence of energetic particle precipitation NO x (EPP-NO x ) interaction with chlorine curbing Antarctic ozone loss - E. M. Gordon; A. Seppälä; B. Funke; J. Tamminen; K. A. Walker (Atmospheric Chemistry and Physics, 2021)
We investigate the impact of the so-called energetic particle precipitation (EPP) indirect effect on lower stratospheric ozone, ClO , and ClONO 2 in the Antarctic springtime. We use observations from the Microwave Limb Sounder (MLS) and Ozone Monitoring Instrument (OMI) on Aura, the Atmospheric Chemistry Experiment – Fourier Transform Spectrometer (ACE-FTS) on SCISAT, and the Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) on Envisat, covering the period from 2005 to 2017. Using the geomagnetic activity index Ap as a proxy for EPP, we find consistent ozone increases with elevated EPP during years with an easterly phase of the quasi-biennial oscillation (QBO) in both OMI and MLS observations. While these increases are the opposite of what has previously been reported at higher altitudes, the pattern in the MLS O 3 follows the typical descent patterns of EPP- NO x . The ozone enhancements are also present in the OMI total O 3 column observations. Analogous to the descent patterns found in O 3 , we also found consistent decreases in springtime MLS ClO following winters with elevated EPP. To verify if this is due to a previously proposed mechanism involving the conversion of ClO to the reservoir species ClONO 2 in reaction with NO 2 , we used ClONO 2 observations from ACE-FTS and MIPAS. As ClO and NO 2 are both catalysts in ozone destruction, the conversion to ClONO 2 would result in an ozone increase. We find a positive correlation between EPP and ClONO 2 in the upper stratosphere in the early spring and in the lower stratosphere in late spring, providing the first observational evidence supporting the previously proposed mechanism relating to EPP- NO x modulating Cl x -driven ozone loss. Our findings suggest that EPP has played an important role in modulating ozone depletion in the last 15 years. As chlorine loading in the polar stratosphere continues to decrease in the future, this buffering mechanism will become less effective, and catalytic ozone destruction by EPP- NO x will likely become a ...